SOA and the art of riding the enterprise service bus the need for the ESB and other infrastructure technologies. - Robinson, Rick
In this article (part 1 of two), I will discuss the role of the enterprise service bus (ESB) and other technologies in providing an infrastructure for service oriented architecture (SOA) in the enterprise. This month, I'll discuss some of the middleware requirements necessary to support a full function SOA. These requirements are driven both by the concepts of SOA and by the need to apply them in enterprise situations. Some of the important middleware capabilities that fulfill these requirements are now characterized as an "enterprise service bus." By examining the requirements, it is possible to identify some key mandatory and optional capabilities for an ESB. These include functions such as data format or protocol translation, support for open standards such as Web services and XML, and the provision of qualities of service such as performance, security and transactionality.